FACTORS AFFECTING ORGANIZATIONAL COMMITMENT - Irma Suryani (Jurnal Manajemen Inovasi, 2018)
Organizational commitment is one of essential elements in achieving organization’s goals. Highly committed employees contribute significant improvement in organization outcomes and goals. Studying what motivate employees to obtain strong commitment is important to enhance organizational performance. The aim of the study is to see what factors affecting organizational commitment using literature review method. Several essential factors are grouped into two perspectives, employers and employee’s perspectives. In employer’s stand point, role ambiguity, job control, job insecurity, career advancement, performance appraisal, and positive team experience have been claimed significantly affecting organizational commitment. In contrast, factors affecting employee’s commitment are locus of control, age and tenure in organization, task self-efficacy, culture, job satisfaction, and employee engagement. Keywords: Organizational commitment,role ambiguity, job control, job insecurity, career advancement, performance appraisal, and positive team experience have been claimed significantly affecting organizational commitment, locus of control, age and tenure in organization, task self-efficacy, culture, job satisfaction, and employee engagement.